Parent–adolescent joint projects involving leisure time and activities during the transition to high school - Marshall, Sheila; Young, Richard; Wozniak, Agnieszka; Lollis, Susan; Tilton-Weaver, Lauree; Nelson, Margo; Goessling, Kristen (Journal of Adolescence, 2014)
Leisure research to date has generally overlooked planning and organizing of leisure time and activities between parents and adolescents. This investigation examined how a sample of Canadian adolescents and their parents jointly constructed and acted on goals related to adolescents' leisure time during the move from elementary to high school. Using the Qualitative Action-Project Method, data were collected over an 8–10 month period from 26 parent–adolescent dyads located in two urban sites, through video-taped conversations about leisure time, video recall interviews, and telephone monitoring interviews. Analysis of the data revealed that the joint projects of the 26 dyads could be grouped into three clusters: a) governance transfer or attempts to shift, from parent to adolescent, responsibility over academic demands, organizing leisure time, and safety with peers, b) balancing extra-curricular activities with family life, academics, and social activities, and c) relationship adjustment or maintenance.